Subunit-specific inhibition of inward-rectifier K+ channels by quinidine - Doi, Tadashi; Fakler, B.; Schultz, Jobst-Hendrik; Ehmke, Heimo; Brändle, U.; Zenner, H.-P.; Süßbrich, H.; Lang, F.; Ruppersberg, J.P.; Busch, A.E. (FEBS letters, 1995)
Distinct inward-rectifier K+ channel subunits were expressed in Xenopus oocytes and tested for their sensitivity to the channel blocker quinidine. The ‘strong’ inward-rectifier K+ channel IRK1 was inhibited by quinidine with an EC50 of 0.7 mM, while the ‘weak’ reactifier channel ROMK1 was only moderately inhibited. ROMK1(N171D)-IRKIC-term chimeric channels, which carry both sites for strong rectification of IRK1 channels (the negatively charged D171 in the second transmembrane domain and the IRK1-C-terminus including E224), displayed strong rectification like IRK1, but showed weak sensitivity to quinidine-like ROMK1, suggesting independence of quinidine binding and rectification mechanisms. Moreover, BIR10 and BIR11, two strong rectifier subunits originally cloned from rat brain, exerted subunit-specific sensitivity to quinidine, being much higher for BIR11. Quinidine blockade of IRK1 was not voltage-dependent, but strongly dependent on the pH in the superfusate. These results strongly suggest a subunit-specific interaction of inward-rectifier K+ channels with neutral quinidine within membrane lipid bilayers.
Elektronische Reproduktion der Druck-Ausgabe 9. März 2000
Gesehen am 25.11.2024